Relationship of Emotional Intelligence to Perceived Stress in Combined Master's of Science and Dietetic Internship Programs. - Frazier, Heather R.; Ocker, Liette B.; Araas, Teresa E.; Blackburn, Sara A. (Journal of Allied Health, 2020)
BACKGROUND: Emotional intelligence (EI) is often studied with perceived stress in students in health professions fields such as nursing but not dietetics. The purpose of this study was to explore the relationship of EI to perceived stress in graduate dietetic students in Combined Master's of Science (MS) and Dietetic Internship (DI) programs. METHODS: EI and perceived stress were collected using the Schutte EI Scale and Perceived Stress Scale-10, respectively. One hundred and two (n=102) graduate dietetic students were recruited through their program directors. All participants had to be enrolled in, and have completed at least one semester, in an Accreditation Council for Education in Nutrition and Dietetics (ACEND)-accredited combined MS/DI program. RESULTS: Graduate dietetic students with higher EI are more likely to have lower perceived stress (r=-0.305, p=0.002). Females had significantly higher perceived stress scores than males (p=0.011). EI scores between female and males was found to be not significant (p=0.082). Perceived stress was significantly associated with class size (r=0.223, p=0.025). CONCLUSIONS: The findings suggest that graduate dietetic students with higher EI scores have lower self-perceived stress. Increasing EI skills in graduate dietetic students might help reduce stress levels and create better coping skills.